THE LOCAL-GLOBAL INNOVATION OF AN INDONESIAN TOEFL-LIKE GAME: A CULTURAL HYBRIDITY MODEL - Ekawati Marhaenny Dukut (University of Kuningan, 2019)
The door to globalization for an Indonesian product is believed possible only when fulfilling some characteristics of other nation’s culture. To ensure the global popularity of a product, therefore, there is a need of mixing the local with a global culture. The cultural hybridity strategy of mixing local-global scenes is evident in the invention of a TOEFL-like game software, which based itself on a mobile application for its platform. With the platform, the game becomes easily downloadable through Google Playstore. It is innovative as it accommodates the Generation Z’s characteristics who are digital savvy. In the game, an animation is created for Listening section which takes in some forms of Javanese culture that are made hybrid with some American and Japanese ones. In finding out how successful the game is in fulfilling the needs of TOEFL-like game players, a Technology Accepted Model questionnaire is given to students from Indonesia and Japan. Japanese players, who are English Department students, were chosen on the assumption that they are more digital savvy. This article reports that the game is useful and beneficial in raising the English competence of both Indonesian and Japanese students. With the cultural hybridity strategy in creating the animation, the players agree that the game is a good model for learning about the English language in a fun and innovative way.